1973
DOI: 10.1071/ch9731545
|View full text |Cite
|
Sign up to set email alerts
|

The aggregation of the tetrasodium salt of copper phthalocyanine 4,4',4'',4'''-tetrasulphonic acid. Diffusion studies

Abstract: The effect of urea and thiourea on the aggregation of copper phthalocyanine-4,4',4",4"'-tetrasulphonic acid in aqueous solution has been studied using the capillary diffusion technique. The addition of excess inert electrolyte was necessary in order that the measurements were not complicated by facilitated diffusion. The extent of aggregation has been estimated empirically from the dependence of the diffusion coefficient on molecular weight. The significance of both the changes in diffusion coefficient and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…[168] The literature presents several interesting articles based on synthesis, characterization, and reactivity of phthalocyanines and metallophthalocyanines. [143][144][145][146][169][170][171][172][173][174][175][176][177][178][179][180][181][182] However, mainly in the last years, the studies about the application of these compounds in PDT have gained more emphasis. Aluminium phthalocyanine chloride is an example of a metallophthalocyanine with good preliminary results regarding applications in PDT.…”
Section: Phthalocyanines and Metallophthalocyaninesmentioning
confidence: 99%
See 2 more Smart Citations
“…[168] The literature presents several interesting articles based on synthesis, characterization, and reactivity of phthalocyanines and metallophthalocyanines. [143][144][145][146][169][170][171][172][173][174][175][176][177][178][179][180][181][182] However, mainly in the last years, the studies about the application of these compounds in PDT have gained more emphasis. Aluminium phthalocyanine chloride is an example of a metallophthalocyanine with good preliminary results regarding applications in PDT.…”
Section: Phthalocyanines and Metallophthalocyaninesmentioning
confidence: 99%
“…A substantial number of investigations have focussed on the aggregation behaviour of substituted phthalocyanines in various solvent systems in which the aggregation number and some thermodynamic parameters were determined. [178,179,185] Sulfonated metallophthalocyanines (MPc) complexes, for instance, frequently form dimers or higher aggregates in solution. [192] Aggregation in these complexes is easily characterized by UV-visible spectroscopy.…”
Section: Phthalocyanines and Metallophthalocyaninesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some MPc systems bind one or two axial ligands; such coordination can have a major effect upon the observed redox activity [4][5][6][7][8][9][10]. On the other hand, many phthalocyanines (Pcs) may aggregate to a greater or lesser extent, and aggregation can influence the observed redox potentials [11][12][13]. However, most unsubstituted MPc species have only very limited solubility in virtually all solvents, thereby limiting solution phase redox measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relevant results obtained from the treatment of biofilms with AM, the experimental group that achieved the greatest logarithmic reduction and decrease in metabolic activity in the present study was the association of AM with aPDT (AM+aPDT). As a hypothesis to be further investigated, considering the excellent antimicrobial potential resulting from the synergism of these two treatments, there is a possibility that AM plays a surfactant role, causing a slight breakdown of the PHTALOX ® solution and improving its photodynamic action, considering that the phthalocyanines exhibit a high aggregation tendency, and the PS that form aggregates have a lower photosensitization efficiency, as aggregation reduces the excitation lifetime of the molecule [ 55 , 56 , 57 ]. The surfactant capacity of AM has already been demonstrated in the study by Lemke et al (2017), in which the authors identified that the cells that make up the AM contain lamellar bodies and express all four surfactant proteins, in addition to having essential lipid species found in the pulmonary surfactant in both amniotic sub regions [ 58 ].…”
Section: Discussionmentioning
confidence: 99%